Spontaneous currents in Josephson junctions between unconventional superconductors and d-wave qubits (Review Article) - Kolesnichenko, Yu.A.; Omelyanchouk, A.N.; Zagoskin, A.M. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2004)
The modern physics of superconductivity can be called the physics of unconventional superconductivity.
The discovery of the d-wave symmetry of the order parameter in high-temperature superconductors
and the triplet superconductivity in compound Sr₂RuO₄ has caused a huge stream of
theoretical and experimental investigations of unconventional superconductors. In this review we
discuss novel aspects of Josephson effect related to the symmetry of the order parameter. The most
intriguing of them is spontaneous current generation in an unconventional weak link. The example
of a Josephson junction as a grain boundary between two disorientated d-wave or f-wave superconductors,
is considered in detail. Josephson current–phase relations and the phase dependences of
the spontaneous current, that flows along the interface are analyzed. The spontaneous current and
spontaneous phase difference are manifestations of the time-reversal symmetry (T ) breaking states
in the system. We analyzed the region of appearance of T -breaking states as function of temperature
and mismatch angle. A review of the basics of superconducting qubits with emphasis on specific
properties of d-wave qubits is given. Recent results in the problem of decoherence in d-wave
qubits, which is the major concern for any qubit realization, are presented.